Easy Service Emergency Call Center Application for Emergency First Aid Knowledge in Modelomo Village Community - Pomalango, Zulkifli B; Rahim, Nirwanto K (PT.Mantaya Idea Batara, 2025)
A total of 36 cases of traffic accidents occurred in January 2024, while in February there were 25 cases of accidents in Gorontalo Regency. Initial data indicates that many people are still unaware of how to provide first aid in the event of an accident. To address this, the development of an Android-based first aid education application has been implemented, offering significant benefitsto Android smartphone clients in getting data on to begin with help measures during accidents.The objective of this research is to analyze the impact of the Easy Service Emergency call center application on the knowledge of emergency first aid among the residents of Modelomo Village. This study uses a pre-experimental research design with a one-group pretest-posttest design. This study was conducted in Modelomo Village, Tiamuta District, Gorontalo Regency. The research was conducted from February to March 2024. The targeted outcome of this research is to demonstrate the utilization of the Easy Service Emergency call center application in improving the community's knowledge of emergency first aid in Modelomo Village, thereby potentially reducing the incidence and impact of traffic accidents at an early stage.